Who opts to study lower secondary teaching? Career-choice in light of socio-economic background, educational interest and subject centred orientation - Keck Frei, Andrea; Berweger, Simone; Denzler, Stefan; Bieri Buschor, Christine; Kappler, Christa (Swiss Journal of Educational Research, 2018)
This paper focuses on the self-selection into teacher education studies and investigates the differences between prospective students choosing between primary teaching and lower secondary teaching. The results show that high school graduates interested in teacher education differ from other high school graduates in their socio-economic background, their academic performance (grades in German) and their time preference. Furthermore, students who choose lower secondary teaching are more interested in subject specific factors (content), while students who choose primary teaching are more student-centered.